Fourier transform infrared (FTIR) analysis identifies microplastics in stranded common dolphins (Delphinus delphis) from New Zealand waters. (December 2021) - Stockin, Karen A.; Pantos, Olga; Betty, Emma L.; Pawley, Matthew D.M.; Doake, Fraser; Masterton, Hayden; Palmer, Emily I.; Perrott, Matthew R.; Nelms, Sarah E.; Machovsky-Capuska, Gabriel E.
Abstract: Here we provide a first assessment of microplastics (MPs) in stomach contents of 15 common dolphins ( Delphinus delphis ) from both single and mass stranding events along the New Zealand coast between 2019 and 2020. MPs were observed in all examined individuals, with an average of 7.8 pieces per stomach. Most MPs were fragments (77%, n = 90) as opposed to fibres (23%, n = 27), with translucent/clear (46%) the most prevalent colour. Fourier transform infrared (FTIR) spectroscopy revealed polyethylene terephthalate (65%) as the most predominant polymer in fibres, whereas polypropylene (31%) and acrylonitrile butadiene styrene (20%) were more frequently recorded as fragments. Mean fragment and fibre size was 584 μm and 1567 μm, respectively. No correlation between total number of MPs and biological parameters (total body length, age, sexual maturity, axillary girth, or blubber thickness) was observed, with similar levels of MPs observed between each of the mass stranding events. Considering MPs are being increasingly linked to a wide range of deleterious effects across taxa, these findings in a typically pelagic marine sentinel species warrants further investigation. Highlights: First FTIR assessment of microplastics in South Pacific cetaceans demonstrates ubiquitous ingestion. Polyethylene terephthalate, polypropylene, and acrylonitrile butadiene styrene were the most representative polymers. Fragments were the most common morphotype of microplastics, with translucent microplastics most detected. No correlation between total microplastic count and any of the measured biological parameters in dolphins was detected.